Efficacy of fructooligosaccharide versus placebo for treatment of acute diarrhea in children: A double-blind randomized clinical trial - Reni Suryanty; Supriatmo Supriatmo; Berlian Hasibuan; Atan Baas Sinuhaji (Indonesian Pediatric Society Publishing House, 2016)
Objective To compare the efficacy of fructooligosaccharide (FOS) versus placebo in pediatric patients with acute diarrhea with re- gard to duration and frequency of diarrhea and the volume and consistency of the stools. Methods This double-blind randomized clinical trial was carried out from July to November 2003 in the pediatric intensive care unit, outpatient clinic, and pediatric ward of Adam Malik Hospital and Pirngadi Hospital, Medan. Subjects were children and infants aged 4 to 24 months suffering from acute diarrhea without dehy- dration or with mild to moderate dehydration whose parents gave consent. Children included in this trial received tablets of either 600 mg FOS or 761 mg fructulin as placebo. Patients with mild to moderate dehydration were initially rehydrated according to the WHO protocol. Afterwards, 10 tablets of FOS or placebo were given to each subject to be taken twice daily. In subjects without dehy- dration, the tablets were given by their parents. Daily follow-up was performed, in which body weight, temperature, duration and frequency of diarrhea, and the volume and consistency of stools were recorded. For outpatients, home visits were made. Results Out of 142 children who met inclusion criteria, 135 com- pleted the study. These consisted of 68 children in the FOS group and 67 in the placebo group. Subjects were mostly <12 months of age (57.0%), male (57.8%), and moderately malnourished (34.1%). There was no statistically significant difference between both groups in the duration and frequency of diarrhea and the volume and con- sistency of stools (P>0.05). Conclusion There is no effect of the administration of FOS as supplemental therapy on the duration and frequency of diarrhea and on the volume and consistency of stools in children with acute diarrhea